2010
DOI: 10.1128/jvi.00889-10
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic Recombination as a Mechanism of Genetic Diversity in Bluetongue Virus

Abstract: Bluetongue (BT), caused by Bluetongue virus (BTV), is an economically important disease affecting sheep, deer, cattle, and goats. Since 1998, a series of BT outbreaks have spread across much of southern and central Europe. To study why the epidemiology of the virus happens to change, it is important to fully know the mechanisms resulting in its genetic diversity. Gene mutation and segment reassortment have been considered as the key forces driving the evolution of BTV. However, it is still unknown whether intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 63 publications
0
50
1
Order By: Relevance
“…Hence, it is logical to expect that the number of intragenic recombination events may be similar to the number of intergenic ones although an unknown proportion of intragenic recombination may be deleterious or lethal. Despite this possibility, its role in the evolution of species, largely underestimated until recent advances in molecular and computation technologies, has been shown to be of great importance occurring in almost all species and kingdoms ranging from virus (He & Ding, 2012; He et al., 2010; Phan, Okitsu, Maneekarn, & Ushijima, 2007) to protists (Ferreira & Briones, 2012), fungi (Stergiopoulos et al., 2014), plants (Kelly et al., 2010; Ortega, Bošković, Sargent, & Tobutt, 2006; Städler & Delph, 2002), and animals (Godinho, Mendonça, Crespo, & Ferrand, 2006; Marthaler et al., 2014). In the current study, we have two lines of evidence to support the hypothesis that intragenic recombination also contributes to the high genetic variation and evolutionary potential of Avr3a.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is logical to expect that the number of intragenic recombination events may be similar to the number of intergenic ones although an unknown proportion of intragenic recombination may be deleterious or lethal. Despite this possibility, its role in the evolution of species, largely underestimated until recent advances in molecular and computation technologies, has been shown to be of great importance occurring in almost all species and kingdoms ranging from virus (He & Ding, 2012; He et al., 2010; Phan, Okitsu, Maneekarn, & Ushijima, 2007) to protists (Ferreira & Briones, 2012), fungi (Stergiopoulos et al., 2014), plants (Kelly et al., 2010; Ortega, Bošković, Sargent, & Tobutt, 2006; Städler & Delph, 2002), and animals (Godinho, Mendonça, Crespo, & Ferrand, 2006; Marthaler et al., 2014). In the current study, we have two lines of evidence to support the hypothesis that intragenic recombination also contributes to the high genetic variation and evolutionary potential of Avr3a.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly it was found that several BTV strains isolated at different time points and from different geographical locations contained genome segments that appeared to be descended from common mosaic ancestors indicating that recombinant genes had become fixed amongst dominant strains in the field. This observation suggests (but does not prove) that the acquisition of the recombinant genes by these dominant field strains may have resulted in an increased evolutionary fitness of these viruses in the field (He et al, 2010).…”
Section: Bluetongue Virus Evolutionmentioning
confidence: 84%
“…Analysis of 690 complete BTV gene sequences available on Genbank, representing all of the genome segments of the virus has indicated that up to 1.6% of the analyzed sequences represented unique recombination events (He et al, 2010). Recombination was found to have occurred in all of the viral genome segments except segments 5 and 6, with recombinants having undergone either single, double or multiple cross-over events.…”
Section: Bluetongue Virus Evolutionmentioning
confidence: 99%
See 2 more Smart Citations